METHODS FOR DETERMINING THE LEVEL OF ARTISTIC AND CREATIVE COMPETENCE OF FUTURE TEACHERS BASED ON THE ARTPEDAGOGICAL APPROACH - Madina Nasritdinova (Western European Studies, 2025)
This article provides a theoretical and practical analysis of the issue of determining the level of artistic and creative competence of future teachers based on the art-pedagogical approach. The study relies on the normative and legal documents adopted by the Government of the Republic of Uzbekistan in the field of education and culture, particularly the requirements of the Law “On Education.” The article reveals the essence of art pedagogy, its significance in the educational process, and presents diagnostic criteria and indicators for assessing the artistic and creative competence of future teachers. It substantiates the necessity of applying artpedagogical methods, observation, testing, and reflective analysis to identify the aesthetic, emotional, and creative development of an individual. The research results contribute to the improvement of innovative approaches aimed at developing creative potential through art within the education system
Keywords: art pedagogy; artistic and creative competence; future teacher